2013
DOI: 10.1007/s12307-013-0135-1
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer with Gastrointestinal Metastasis - Review of Theories of Metastasis with Three Rare Case Descriptions

Abstract: Approximately 1 in 14 men and women during their lifetime will be diagnosed with lung cancer, which is the leading cause of cancer-related mortality in the world. As of January 1, 2008, there were about 373,500 men and women living with lung cancer in the United States. Fewer than 60,000 of these are estimated to be alive by January 2013, reflecting a poor overall 5-year relative survival rate of under 16 %. With metastatic cancer, the overall 5-year survival is meager 4 %. On the other hand, the overall five-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 54 publications
0
13
0
2
Order By: Relevance
“…Squamous cell carcinoma is known to be more aggressive with an associated poor prognosis. 3 This is supported by the fact that adenocarcinoma of the lung presents with fewer incidences of GI metastatic lesions in the study by Antler et al, at the same time as having more responsive treatment via erlotinib for cells mutated for epidermal growth factor receptor (EGFR) and crizotinib for cells mutated in anaplastic lymphoma kinase (ALK). 3 One concern with treating GI metastases from lung cancers is the risk of chemotherapy-induced perforation.…”
Section: Complications and Managementmentioning
confidence: 90%
See 2 more Smart Citations
“…Squamous cell carcinoma is known to be more aggressive with an associated poor prognosis. 3 This is supported by the fact that adenocarcinoma of the lung presents with fewer incidences of GI metastatic lesions in the study by Antler et al, at the same time as having more responsive treatment via erlotinib for cells mutated for epidermal growth factor receptor (EGFR) and crizotinib for cells mutated in anaplastic lymphoma kinase (ALK). 3 One concern with treating GI metastases from lung cancers is the risk of chemotherapy-induced perforation.…”
Section: Complications and Managementmentioning
confidence: 90%
“…It has been estimated that there is a 4.6-14% incidence of GI metastasis found at autopsy (see Table 3). 11,31,34,39 Antler et al, 34 Yoshimoto et al, 41 and Burbige et al 40 42 This may due to the fact that this study was limited to the adenocarcinoma histology alone; it is known to be less aggressive than squamous cell carcinoma, 3 and constitutes a lower proportion of lung cancer patients demonstrating such metastatic disease and has shown a lower metastatic rate (see Table 1). Additionally, Stenbygaard's postmortem study only quantified the number of metastatic lesions to the small bowel without evaluating other parts of the GI tract.…”
Section: Comparison Of Clinical Cases With Post-mortem Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Las metástasis de intestino delgado en el carcinoma primitivo de pulmón son excepcionales y sus manifestaciones clí-nicas raras 2 . Cuando éstas se producen, pueden causar hemorragia, malabsorción, perforación intestinal, o incluso invaginación intestinal 3,4 aunque la forma más frecuente de presentación es la suboclusión-obstrucción intestinal 5 .…”
unclassified
“…Sakai et al noted that only 12 lung cancer cases with metastases to the large intestine have been reported in published case reports as of 2012 [5, 6, 1624]. In our literature review, we found four additional cases that had been recently published [1, 25, 26]. In the 17 documented cases, including these 16 previous cases and our case, the median age was 63 years (43–80 years), and there is a clear male predominance ( N = 15, 88.2%).…”
Section: Discussionmentioning
confidence: 71%